109 What mattersto me?: development and use of a person centred outcome measure (pcom) for parents of children with feeding disorders. (4th October 2017) - Bryant-Waugh, R; Cooke, L; Harris, M; Mora, M; Withers, F
Abstract : Background: NHS England's Five Year Forward View sets out how the health service needs to change, arguing for "a more engaged relationship with patients, carers and citizens so that we can promote wellbeing and prevent ill-health". Underpinning this transformation is the expectation that "When people do need health services, patients will gain far greater control of their own healthcare." The recent emphasis on Person (or Patient) Centred Outcome Measures (PCOMs) reflects this shift, as PCOMs are measures of outcome areas that are identified as important solely by the patient or their parent(s)/or carer(s). Research suggests that in a significant number of cases of feeding disorders, clinicians do not address parental concerns, despite evidence demonstrating that families reliably identify issues that require treatment. We know that feeding difficulties are associated with high levels of parental anxiety and mealtime conflict which may increase risk of a range of additional problems. This makes timely and appropriate attention to issues that matter most to those affected extremely important. Project description: The primary aim of this project was to develop a parent PCOM relevant to childhood feeding disorders that is evidence-based, systematically-derived and has high face validity. The project was completed over three phases in the GOSH Feeding Disorders Service. We report on the design, implementation and results of the project, which included direct input from 122 parents/carers whose children are treated by the Feeding Disorders Team. Results: The work of clinical staff, researchers and families resulted in a PCOM 'What Matters To Me?', which surveys parents and carers on the very themes the participating group identified as most salient. The outcomes will include description of the subsequent routine use of the measure, now in electronic format, administered as part of clinic protocol at the start of contact and again when the patient is discharged.